Post-Weaning Breast Milk HIV-1 Viral Load, Blood Prolactin Levels and Breast Milk Volume - Thea, Donald M. (2006)
BACKGROUND: The effect of abrupt weaning, advocated as a safe transition from exclusive breastfeeding in HIV-exposed children, on the quantity of HIV viral load in breast milk (BMVL) is not known. OBJECTIVES: To determine the effect of abrupt cessation of breastfeeding on serum prolactin, pumped breast milk volume and BMVL obtained 2 weeks after rapid weaning in HIV-infected women. METHODS: Women enrolled in a prospective study (ZEBS) were randomized to abruptly wean at 20 weeks postpartum or continue exclusive breastfeeding. Breast milk was obtained at 22 weeks by electric breast pump over 10 min from 222 women who had either weaned or continued to breastfeed. Pre- and post-pumping prolactin was measured. BMVL was measured at 20 and 22 weeks in 71 randomly selected women from both groups. RESULTS: Baseline prolactin and breast milk volume was significantly lower among women who had weaned. Detectable (68 versus 42%; P 0.03) and median BMVL (448 versus < 50 copies/ml; P = 0.005) was significantly higher = among those who had weaned in comparison with those who were still breastfeeding and was significantly higher in the same women after weaning compared with 2 weeks earlier (P = 0.001). Conclusions: BMVL is substantially higher after rapid weaning and this may pose an increased risk of HIV transmission if children resume breastfeeding after a period of cessation. Increases in BMVL with differing degrees of mixed feeding needs to be assessed.